ROBOT PENYORTIR BENDA BERDASARKAN WARNA MENGGUNAKAN SENSOR WARNA TCS3200 - Yudhi Andrian (SISFOTENIKA, 2013)
Abstract : Color Based Sortir Robot Using TCS3200 Color Sensor. A robot arm that can sort objects based on color has been designed. Color sensor that has been used is TCS3200 that can recognize RGB color of an object. Objects that will be sorted, it’s moved by conveyor to the color objects reading room. When the infrared sensor hit the object, the conveyor will stop, so that the position of the object is exact below the color sensor then the color sensor reads the object color. DFRobot Adjustable Infrared Sensor Switch is used to determine whether the objects that have come out of the color reading room was ready to lifted by a robotic arm to be moved into the place. Robot arm consists of 4 pieces of servo, that each has a different function. A robot arm consists of gripper, elbow, shoulder, and site. From the research it can be concluded that the TCS3200 sensor can read RGB color of objects very well, a very small percentage of errors reading that’s 0.04%, a very high of sensor accuracy that’s reaches 99.96%. Keywords: Color Sensor, Robot Arm, Microcontroller, AVR ATMega8535, TAOSTM TCS3200D, DT Sense Color